PENGARUH LUMPUR TERHADAP KEPADATAN DAN PERMEABILITAS PASIR MUNTILAN - Bambang Widodo; Vemi Widoanindyawati (Wahana Teknik Sipil: Jurnal Pengembangan Teknik Sipil, 2026)
Soil permeability controls the ability of water to pass through voids in soil. Muntilan sand is widely used as a construction material, yet its relatively open gradation may produce high seepage when applied as fill or drainage-related material. This paper evaluates the effect of mud content on the compaction characteristics and permeability of Muntilan sand using laboratory testing. The study used sand from Kecamatan Dukun, Kabupaten Magelang, and mixed it with mud at 0%, 5%, 10%, 20%, and 40% by weight. Physical testing consisted of water content, specific gravity, grain-size distribution, and unit weight. Mechanical testing used the Standard Proctor method, while hydraulic testing used the constant-head permeability method for granular soil. The test results indicate that increasing mud content raised the maximum dry density from 1.903 g/cm³ in original sand to 2.180 g/cm³ at 40% mud. Conversely, the coefficient of permeability decreased from 6.5862 x 10⁻ ³ cm/s in original sand to 7.6982 x 10⁻4 cm/s at 40% mud. The decrease is attributed to fine particles filling the pore space of the sand skeleton. These results show that mud addition can reduce seepage potential but must be controlled to avoid drainage and surface ponding problems.